Knowledge, Attitude and Feeding Practices among the Mothers having Under-5 Children in a Rural Community of Bangladesh (Ibrahim Medical College Journal, 2009)
Ibrahim Med. Coll. J. 2008; 2(1): 35 doi: 10.3329/imcj.v2i1.2931